Vegetal Cover and Soil Conservation Values of Three Common Grasses along the Ravineland of Kunwari Catchment Area, Morena (M.P.) - Sharma, D.P.; Maury, A.N.; Sharma, Kamlesh (Journal of Soil and Water Conservation, 2022)
Soils of the ravineland are sandy-loam with major proportion of sand (highest 76.4%). Silt and clay are present in almost equal proportion. The soils with low nitrogen (5.73 - 13.90 mg/100g) and phosphorus (0.07 - 0.20 mg/g), do not support healthy vegetation. In an area in Morena, Madhya Pradesh, representative of the above characteristics, experiment was conducted to study the soil loss under different plant covers and compare it with the soil loss from bare plot. iseilema laxum and Desmostachya bipinnata are the good soil binding grasses with very high soil consen-ation values from 79.9 to 89.4% and 66.9 to 76.9% respectively along the different substrata of the ravineland which are highly prone to erosive forces of water. Aristida adscensionis with very low vegetal cover (4.01 to 8.79 cm2/m2) has poor conservation values (5.9 to 13.6%).